The influence of nurse characteristics on practice skills and attitudes towards working with families in critical care: A regression analysis. (October 2022) - Zwicky, Anja; Thaqi, Qendresa; Hediger, Hannele; Naef, Rahel
Abstract: Objectives: The study aimed to identify nurse characteristics that influence their self-perceived practice skills in working with families and their attitudes towards engaging families in adult and neonatal intensive care units. Research methodology/Design: Secondary data analysis using a descriptive, cross-sectional design. Setting: An online survey was completed by 256 nurses from six adult intensive (73% response rate) and two neonatal intensive and one intermediate care unit (27% response rate) in a Swiss, university affiliated hospital. Main outcome measures: Nurses' self-perceived practice skills in working with families were assessed with the "Family Nursing Practice Scale". Attitudes towards families were measured with the "Families' Importance in Nursing Care – Nurses' Attitudes Scale". Data were analysed with multiple linear regression models. Results: Prior education in family nursing significantly influenced nurses' self-perceived practice skills in working with families. Nurses' clinical speciality had a significant influence on their attitudes towards overall, and on the subscale "family as a burden". Neonatal intensive care nurses showed more open attitudes towards families overall, but perceived family more often as a burden than nurses in adult intensive care. Nurses' perceived skills and attitudes in family engagement significantly influenced each other. Conclusion: The results suggest that nurses' prior education in family nursing and clinical speciality determine their ability to work with and engage families in critical care. Our study suggests that integration of family nursing engagement practices in critical care requires educational implementation strategies combined with culture change efforts.